Thermal expansion model for cast aluminium silicon carbide - Taufik, R. S.; Sulaiman, Samsudin (Elsevier, 2013)
This paper presents the development of thermal expansion model for casted aluminium silicon carbide. Thermal expansion in the casting process is one of the most important parameters that influence the casting quality. The thermal expansion model for casted aluminium silicon carbide is developed by the squeeze casting method. A model of numbers evolved for the prediction of the unidirectional fibre and matrix reinforced composites was presented. The coefficient of thermal expansion (CTEs) of aluminium silicon carbide fibres reinforced material was significantly influenced by the thermal stresses and interfaces between matrix and fibres. The thermal expansion behaviour of the casted aluminium silicon carbide fibres reinforced composite relies on the thermal expansion of the fibres, and influenced by the onset of interfacial strength and residual stress state. The validation shows a good agreement among the model and experimental result of LM6 alloys silicon reinforces. As the result, the thermal expansion model for casted aluminium silicon carbide could predict the surface roughness of the casting product.